Coupled cluster methods for autoionisation resonances - Sajeev, Y.; Ghosh, A.; Vaval, N.; Pal, S. (International Reviews in Physical Chemistry, 2014)
The quantum chemical calculation of autoionisation resonances in many-electron systems is a highly challenging task due to the ionisation continuum involved. Recently, advances were reported where conventionally used ab initio codes can be employed to compute autoionisation resonances. This is made possible by the use of analytical continuation tools such as complex scaling and complex absorbing potential (CAP) in the electronic structure codes. We review the formulation and the use of complex scaling and CAP in coupled cluster methods for the electron correlated calculation of energy position and autoionisation decay rate of resonance states. The application of analytically continued coupled cluster method for the correlated calculation of interatomic or intermolecular Coulombic decay process is also discussed.
Keywords: autoionisation resonances; complex absorbing potential; complex scaling; equation-of-motion coupled cluster; Fock space multi-reference-coupled cluster; intermolecular Coulombic decay

Relativistic equation-of-motion coupled-cluster method using open-shell reference wavefunction: application to ionization potential - Pathak, H.; Sasmal, S.; Nayak, M. K.; Vaval, N.; Pal, S. (Journal of Chemical Physics, 2016)
The open-shell reference relativistic equation-of-motion coupled-cluster method within its four-component description is successfully implemented with the consideration of single- and double- excitation approximations using the Dirac-Coulomb Hamiltonian. At the first attempt, the implemented method is employed to calculate ionization potential value of heavy atomic (Ag, Cs, Au, Fr, and Lr) and molecular (HgH and PbF) systems, where the effect of relativity does really matter to obtain highly accurate results. Not only the relativistic effect but also the effect of electron correlation is crucial in these heavy atomic and molecular systems. To justify the fact, we have taken two further approximations in the four-component relativistic equation-of-motion framework to quantify how the effect of electron correlation plays a role in the calculated values at different levels of theory. All these calculated results are compared with the available experimental data as well as with other theoretically calculated values to judge the extent of accuracy obtained in our calculations.

Electron–nucleus scalar–pseudoscalar interaction in PbF: Z-vector study in the relativistic coupled-cluster framework - Sasmal, S.; Talukdar, K.; Nayak, M.K.; Vaval, N.; Pal, S. (Molecular Physics, 2017)
The scalar–pseudoscalar interaction constant of PbF in its ground state electronic configuration is calculated using the Z-vector method in the relativistic coupled-cluster framework. The precise calculated value is very important to set upper bound limit on (Formula presented.)-odd scalar–pseudoscalar interaction constant, ks, from the experimentally observed (Formula presented.)-odd frequency shift. Further, the ratio of the effective electric field to the scalar–pseudoscalar interaction constant is also calculated which is required to get an independent upper bound limit of electric dipole moment of electron, de, and ks and how these (de and ks) are interrelated is also presented here. © 2017 Informa UK Limited, trading as Taylor & Francis Group

Effect of protonation and deprotonation on electron transfer mediated decay and interatomic coulombic decay - Kumar, R.; Vaval, N. (ChemPhysChem, 2023)
Electronically excited atoms or molecules in an environment are often subject to interatomic/intermolecular Coulombic decay (ICD) and/or electron transfer mediated decay (ETMD) mechanisms. A few of the numerous variables that can impact these non-radiative decay mechanisms include bond distance, the number of nearby atoms or molecules, and the polarisation effect. In this paper, we have studied the effect of protonation and deprotonation on the ionization potential (IP), double ionization potential (DIP), and lifetime (or decay width) of the temporary bound state in these non-radiative decay processes. We have chosen LiH-NH3 and LiH-H2O as test systems. The equation of motion coupled cluster singles and doubles method augmented by complex absorbing potential (CAP-EOM-CCSD) has been used in calculating the energetic position of the decaying state and the system's decay rate. Deprotonation of LiH-NH3/LiH-H2O either from the metal center (LiH) or from ammonia/water lowers the IP and DIP compared to the neutral systems. In contrast, protonation increases these quantities compared to neutral systems. The protonation closes the inner valence state relaxation channels for ICD/ETMD. For example, the decay of the O-2s/N-2s state stops in protonated systems (LiH2+-H2O, LiH2+-NH3, and LiH-NH4+). Our study also shows that the efficiency, i. e., the rate of ICD/ETMD, can be altered by protonation and deprotonation. It is expected to have implications for chemical and biological systems.